IMPLEMENTASI METODE WAHDAH DALAM MENINGKATKAN HAFALAN AL- QUR’AN SANTRI DI PONDOK PESANTREN BABUSSALAM KALIBENING MOJOAGUNG JOMBANG - Usmanto; Burhanuddin Ridlwan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The ability to read the Qur'an well and correctly is one of the basic competencies that every student must have. However, in practice, many students are still found to experience errors in tajwid, makharijul huruf, and reading fluency. Inappropriate learning methods are often one of the factors causing low reading quality. This study aims to describe the Implementation of the Wahdah Method in Improving the memorization of the Qur'an of Students at the Babussalam Kalibening Mojoagung Jombang Islamic Boarding School. This study uses a qualitative approach with a descriptive type. The results of the study show that the implementation of learning using the wahdah method in improving the memorization of the Qur'an at the Babussalam Kalibening Mojoagung Jombang Islamic Boarding School is carried out through several stages, namely: the teacher reads/exemplifies the reading first repeatedly, then the students imitate the reading that has been read by the teacher in groups, then the teacher appoints the students to read one by one or by coming forward in front of him. Supporting factors for learning using the Wahdah method to improve Quran memorization include teachers with clear sanads, innovative and interactive teachers, and a conducive environment. Inhibiting factors include a lack of motivation within the students themselves, a lack of communication between teachers and students, and differences in understanding among the students.